Conversational formulae in glottodidactics – case study - Krzyżanowska, Anna; Sułkowska, Monika (Papers in Linguistics, 2023)
The aim of this article is to present results of a study examining the extent of pragmatic competence of Romance Philology and Romance Studies students concerning their knowledge of French conversational formulae. As well known, such multi-word formulae are difficult and cumbersome when learning a foreign language, as well as being hard to translate in texts from one language into another. In the first part of the article, the concept of formula is defined referring to recent studies of French and Polish phraseology. Then, the questionnaires are analysed as regards the data obtained on the number of correctly (or incorrectly) given equivalent formulae. What is more, qualitative analysis of all the questionnaires made it possible to show the different mechanisms of selection of equivalents conditioned, for instance, by the global meaning or literal sense of a given formula, as well as imitation of its structure. The undertaken research showed difficulties in selecting adequate correlates, which confirms the initial hypothesis on the special status of multi-word conversational formulae, and therefore entails non-native speakers’ need to develop specific competences.